Relationship Between COVID-19 Related Knowledge and Anxiety Among University Students: Exploring the Moderating Roles of School Climate and Coping Strategies - Quansah, Frank; Hagan, John E.; Ankomah, Francis; Srem-Sai, Medina; Frimpong, James B.; Sambah, Francis; Schack, Thomas (Frontiers in Psychology, 2022)
The emergence of the COVID-19 pandemic resulted in abrupt disruptions in teaching and learning activities in higher education, with students from diverse programs suffering varying levels of anxieties. The physical education field happens to be one of the most affected academic areas due to its experiential content as a medium of instruction. In this study, we investigated the roles of school climate and coping strategies in the relationship between COVID-19 related knowledge and anxiety. Through the census approach, a cross-sectional sample of 760 students was administered a questionnaire in two universities offering Physical Education in Ghana: the University of Education, Winneba, and University of Cape Coast. The outcome of the study found a positive and significant link between COVID-19 knowledge and anxiety. Further, school climate and coping strategies significantly moderated the relationship between students’ COVID-19 knowledge and associated anxiety. The findings have implications for creating a conducive school environment that reduces the risk of COVID-19 infection and through students’ adoption of active coping strategies in an attempt to reduce psychological distress associated with COVID-19 anxiety.